Penerapan Model Role Playing Berbantuan Media Komik untuk Meningkatkan Hasil Belajar Bahasa Indonesia pada Peserta Didik Kelas V SDN-1 Telangkah Tahun Pelajaran 2016/2017: Application of Role Playing Model Assisted by Media Comics to Improve Indonesian Language Learning Outcomes in Grade V Students of SDN-1 Telangkah 2016/2017 Academic Year - Agustin Dwi Utami; Dedy Setyawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to describe the activities of fifth-grade students of SDN Telangkah-1 in learning the Indonesian language by using role-playing models assisted by comic media as well as improving Indonesian language learning outcomes of fifth-grade students of SDN-1 Telangkah by using role-playing models supported by humorous media participants fifth-grade students of SDN-1 Telangkah. The method used by the researcher was Classroom Action Research (CAR) with research subjects 31 students consisting of 12 men and 19 female class V SDN-1 Telangkah. Data collection techniques in this study used observation and tests. Data analysis uses qualitative and quantitative data analysis. The results of this study indicate that the activities of fifth-grade students of SDN-1 Telangkah at the time of learning took place by using a role-playing model assisted by comic media on Indonesian language subjects about material Playing the Drama in the first cycle was in an outstanding category. Also, there was an increase in the results of learning the Indonesian Language by applying the role-playing model assisted by comic media to the fifth-grade students of SDN-1 Telangkah. This can be seen from the learning outcomes data of students, in the pre-test, the average score of 61 with classical completeness was 45.16%, while the post-test results in the first cycle the average rating of 78 and integrity in the traditional, i.e. 100%.